Resistance of agricultural pests to synthetic insecticides in Colombia: A review - Pineda, Maria; Bacca, Tito (Revista de Ciencias Agrícolas, 2025)
The phenomenon of insecticide resistance is defined as the ability of insect populations to develop the capacity to survive doses of insecticides that would otherwise be lethal. This phenomenon can be attributed to the natural selection of individuals with genetic mutations that confer resistance. A comprehensive understanding of insecticide resistance mechanisms is crucial for developing novel control strategies within existing integrated pest management plans. In this context, this review examines the research conducted to characterize the resistance of agricultural pests (insects/mites) to insecticides/acaricides in Colombia. A search of relevant scientific literature was conducted using keywords in the databases. A literature review revealed that, according to reports from Colombia, there have been 27 documented instances of insecticide/acaricide resistance across 12 species. Conversely, the Arthropod Pesticide Resistance Database (APRD) indicates the existence of 98 reports of resistance to insecticides/acaricides distributed across 10 species. A single instance of acaricide resistance was identified in the respiratory target; all other cases demonstrated resistance to the nervous and muscular targets. In this review, we present the main results, which are focused on determining toxicity curves and calculating lethal concentrations. We highlight the research carried out in the last decade, which makes use of new molecular techniques and allows a more detailed view of the resistance mechanisms. Furthermore, we suggest novel methodologies that could be employed to improve current integrated pest management plans.